2015
DOI: 10.1142/s1793292015500721
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis and Photocatalytic Performance of WO3/rGO Nanocomposite for Degradation of 1-Naphthol

Abstract: In this study, WO 3 -rGO nanocomposites were synthesized via a facile chemical method followed by a calcination process. The samples were characterized by UV-Vis spectroscopy, Fourier transform infrared (FT-IR) spectroscopy, Raman spectroscopy, BET technique, scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The results con¯rmed the formation of the nanocomposites. Photocatalytic activity of the synthesized samples was evaluated in degradation of 1-naphthol as a polycyclic aromatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…SMX degradation over rGO-WO 3 -200 was significantly influenced by neutral pH and displayed the pre-eminent process [ 18 ]. Photodegradation of naphthol-1 by rGO-WO 3 –nanocomposite and WO 3 was achieved by 84% and 40% respectively, attributed to the larger specific surface area and lower band gap energy [ 19 ]. Outcomes suggested that the presence of rGO in the nanocomposite enabled the electron transfer [ 19 ].…”
Section: Photocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…SMX degradation over rGO-WO 3 -200 was significantly influenced by neutral pH and displayed the pre-eminent process [ 18 ]. Photodegradation of naphthol-1 by rGO-WO 3 –nanocomposite and WO 3 was achieved by 84% and 40% respectively, attributed to the larger specific surface area and lower band gap energy [ 19 ]. Outcomes suggested that the presence of rGO in the nanocomposite enabled the electron transfer [ 19 ].…”
Section: Photocatalysismentioning
confidence: 99%
“…Photodegradation of naphthol-1 by rGO-WO 3 –nanocomposite and WO 3 was achieved by 84% and 40% respectively, attributed to the larger specific surface area and lower band gap energy [ 19 ]. Outcomes suggested that the presence of rGO in the nanocomposite enabled the electron transfer [ 19 ]. The enhanced photocatalytic activity was due to the synergistic effect between WO 3 and rGO sheets and suppressing the electron-hole pair recombination in the WO 3 -rGO nanocomposite [ 6 ].…”
Section: Photocatalysismentioning
confidence: 99%
“…Tungsten oxide (WO3) is a typical n-type semiconductor that has attracted great attention because of its nontoxicity, stable physicochemical properties, and good resistance to photocorrosion [26][27][28][29][30][31][32][33][34]. Importantly, both theory and experiments have proved that WO3 possesses a relatively low valence-band edge, which endows it with strong oxidation ability and makes it a promising candidate for NO removal [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Graphene is a single layer of sp 2 bonded carbon atoms arranged in a two dimensional honeycomb fashion (Kamat 2010, Xiang, Yu et al 2012, Titirici, White et al 2015. Graphene possesses excellent properties like excellent thermal conductivity (~5,000 W m -1 K -1 ), superior electron mobility (200,000 cm 2 V -1 s -1 ) at ambient temperature and extremely high theoretical specific surface area (~2600 m2g-1) (Schedin, Geim et al 2007, Dato, Radmilovic et al 2008, Xiang, Yu et al 2012, Fu, Xia et al 2015, Hajishafiee, Sangpour et al 2015. Thereby, these outstanding properties make graphene and reduced graphene oxide (RGO) to be excellent candidates serving as co-catalysts in efficient heterogeneous photocatalysts (Kamat 2010, Xiang, Yu et al 2012, Zhang, Yang et al 2013).…”
Section: Graphene-based Semiconductor Photocatalystsmentioning
confidence: 99%
“…As a new carbon material firstly experimentally discovered in 2004, graphene has unique 2D structure, large surface area, excellent electronic and physicochemical properties (Schedin, Geim et al 2007, Dato, Radmilovic et al 2008, Xiang, Yu et al 2012, Fu, Xia et al 2015, Hajishafiee, Sangpour et al 2015. When being employed in a photocatalytic system, graphene and/or RGO can work not only as superior supporting matrixes for bonding functional components but also excellent electron mediators to adjust electron transfer, and thus restrain the recombination of photogenerated charges and subsequently improve the electron-hole separation (Xiang, Yu et al 2012, Huang, Yue et al 2013.…”
Section: Introductionmentioning
confidence: 99%